Retrospective analysis of breast cancer subtypes, risk factors, and lump features: outcomes from a tertiary care hospital in Multan, Pakistan - Anwar, Rana A.; Ali, Huzafa; Khan, Amna; Abbas, Husnain; Ahmed, Mushtaq; Ikram, Faiza; Fatima, Sajil; Akhtar, Saba; Zafar, Minahil; Rashid, Talha; Haseeb, Muhammad; Faizan, Umar (International Journal of Research in Medical Sciences, 2025)
Background: Breast cancer is the most frequently diagnosed malignancy and a leading cause of cancer-related mortality among Pakistani women. Despite its high prevalence, patients in Pakistan are often diagnosed at advanced stages, resulting in poor prognosis. This study aimed to assess the frequency of different breast cancer subtypes, clinical features, staging, grading, and receptor statuses among patients in southern Punjab. Methods: A retrospective analysis was conducted at Nishtar Cancer Center, Multan, from October 2024 to February 2025, using medical records of 193 female patients diagnosed with breast tumors in 2024. Demographic details, risk factors, tumor characteristics, and receptor status were analyzed using statistical package for the social sciences (SPSS) version 26.0. Results: Most patients (47.2%) were aged 40–60 years, with 96.9% being married and 17.6% having a history of breastfeeding. Most tumors were invasive ductal carcinoma (90.7%), commonly located in the upper outer quadrant (69.4%). Advanced-stage disease was prevalent, with T4 tumors (38.3%) and N1 lymph node involvement (43.5%). Grade III tumors were frequent (60.1%), and receptor analysis showed luminal B (31.6%) as the most common subtype, followed by luminal A (30.1%) and triple-negative (25.4%). Conclusions: The findings highlight the late-stage diagnosis and aggressive nature of breast cancer in this region, emphasizing the urgent need for enhanced awareness, early screening programs, and improved healthcare accessibility to facilitate early detection and better treatment outcomes.